2015
DOI: 10.5603/cj.a2015.0014
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance predicts the risk for recurrent coronary events in post-infarction patients

Abstract: (HR 1.5; p = 0.038). The plasma level of plasminogen activator inhibitor-1 was associated with higher risk for recurrent coronary events in patients with insulin resistance (HR 1.79; p = 0.03, interaction p = 0.018). Conclusions: In conclusion, insulin resistance predicts recurrence of coronary events in post--infarction population. HOMA2-IR is better than BMI in stratifying risk of recurrent coronary events. (Cardiol J 2015; 22, 5: 519-526)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…The patients who survive a mild MI need preventive care for heart failure and treatment for the long-term metabolic alterations, including development of IR and IGT, caused by MI [ 5 , 7 , 8 , 10 15 ]. In fact, abnormal glucose tolerance is an independent predictor of cardiovascular events such as recurrent MI, stroke, adverse cardiac remodeling, and heart failure during a median follow-up time up to 34 months post MI [ 18 , 45 47 ]. Similar to what is observed in humans [ 13 ], we show that mild MI led to progressive glucose intolerance in obese mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patients who survive a mild MI need preventive care for heart failure and treatment for the long-term metabolic alterations, including development of IR and IGT, caused by MI [ 5 , 7 , 8 , 10 15 ]. In fact, abnormal glucose tolerance is an independent predictor of cardiovascular events such as recurrent MI, stroke, adverse cardiac remodeling, and heart failure during a median follow-up time up to 34 months post MI [ 18 , 45 47 ]. Similar to what is observed in humans [ 13 ], we show that mild MI led to progressive glucose intolerance in obese mice.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, IR, IGT, and dysglycemia may also contribute to the development of adverse LV remodeling post-MI [ 14 , 16 ] which is recognized as the predominant pathological process in the development of heart failure [ 17 ]. Furthermore, studies have shown direct association between IR, IGT, type 2 diabetes, and increased risk of subsequent MIs and the development of heart failure post-MI [ 11 , 12 , 18 ]. Thus, new therapeutic strategies to reduce the risk of MI-induced insulin resistance, glucose intolerance, and type 2 diabetes are essential to improve life expectancy and quality of life in patients who suffer from MI.…”
Section: Introductionmentioning
confidence: 99%
“…HOMA2-IR may be used to stratify risk for the recurrence of coronary events in the postinfarction population [ 32 ] and predict in-hospital mortality after acute coronary syndrome. [ 33 , 34 ] Previous studies have shown the incidence of adverse cardiac events including mortality rises independently from DM, along with the increase of IR in patients with coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…В недавнем исследовании Iguchi et al был применен метод оптической когерентной томографии, позволяющий детально охарактеризовать структуру атеросклеротической бляшки: было показано, что инсулинорезистентность тесно взаимосвязана с большей склонностью атеросклеротической бляшки к тромбообразованию, что проявлялось меньшей толщиной фиброзной оболочки, большим содержанием липидов в бляшке у группы обследованных лиц с наибольшей выраженностью инсулинорезистентности [9]. В проспективных наблюдениях больных, перенесших острый коронарный синдром, обнаружено, что инсулинорезистентность была сопряжена со значительно худшим прогнозом [10], а также с развитием повторных острых коронарных синдромов [11]. Представляется важным подчеркнуть, что инсулинорезистентность способствует возрастанию риска рестеноза стентов, как было показано в недавнем проспективном исследовании 417 больных, которым было проведено стентирование с помощью DES [12].…”
Section: рис 1 содержание инсулина в плазме крови натощак и через 2unclassified